The visual-attention span deficit in developmental dyslexia: Review of evidence for a visual-attention-based deficit. - Valdois, Sylviane (Dyslexia (10769242), 2022)
The visual attention span (VAS) deficit hypothesis in developmental dyslexia posits that a subset of dyslexic individuals shows a multielement parallel processing deficit due to reduced visual attention capacity. However, the attention-based interpretation of poor performance on VAS tasks is hotly debated. The purpose of the present paper is to clarify this issue through a critical review of relevant behavioural and neurobiological findings. We first examine the plausibility of alternative verbal interpretations of VAS performance, evaluating whether performance on VAS tasks might reflect verbal short-term memory, verbal coding or visual-to-verbal mapping skills. We then focus on the visual dimensions of VAS tasks to question whether VAS primarily reflects visuo-attentional rather than more basic visual skills. Scrutiny of the available behavioural and neurobiological findings not only points to a deficit of visual attention in dyslexic individuals with impaired VAS but further suggests a selective endogenous attentional system deficit that relates to atypical functioning of the brain dorsal attentional network. The overview clarifies the debate on what is being measured through VAS tasks and provides insights on how to interpret the VAS deficit in developmental dyslexia.